Nb3Sn superconducting phase microstructure prediction method based on dynamic data screening
The method of predicting microstructure of Nb3Sn superconducting phase screened through kinetic data solves the problems of time-consuming and abnormal microstructure in the prior art, and realizes rapid prediction of Nb3Sn microstructure and effective screening of phase-forming treatment processes, reducing time costs.
Patent Information
- Application Number
- CN202411811078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
The existing Nb3Sn superconducting process takes a very long time, and the phase processing process is formulated using the "trial and error method", which leads to high time costs and is prone to microstructure abnormalities.
The microstructure prediction method of Nb3Sn superconducting phase screening based on kinetic data is adopted, and Cu-15Sn/Nb composite material is prepared by DC hot press assisted sintering equipment, and phase-forming is performed in a vacuum heat treatment furnace. The thickness and grain size of Nb3Sn layer under different phase-forming processes are counted, and fitted with kinetic formulas is combined to predict the impact of different phase-forming temperatures and times on the proportion and grain size of Nb3Sn.
Effectively predict the impact of different phase-forming treatment processes on the microstructure of Nb3Sn, reduce the time cost of batch tests, avoid microstructure abnormalities caused by process instability, and guide the rapid screening of Nb3Sn phase-forming treatment processes.
Smart Images

Figure CN119694443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superconducting material microstructure prediction methods, and relates to a Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening. Background Art
[0002] Nb3Sn superconducting wire has the characteristics of high critical temperature, upper critical magnetic field and critical current density, and is one of the ideal materials for winding high-field superconducting magnets above 10T. The process of preparing Nb3Sn superconducting wire by bronze method is relatively complicated. By assembling high-purity Nb rods and "lotus root-shaped" porous CuSn alloy, a linear CuSn / Nb precursor is obtained after multiple deformations, and then a long-term phase treatment is carried out to generate Nb3Sn superconducting phase at the CuSn / Nb interface, so that the wire has superconducting properties. Related research results show that superconducting wires with a higher Nb3Sn ratio and a relatively small Nb3Sn grain size usually have excellent critical current density. Therefore, it is key to improve the critical current density of superconducting wires by optimizing the phase treatment process to control the Nb3Sn ratio and its grain size.
[0003] In fact, the Nb3Sn ratio and grain size are positively correlated with the phase treatment time and temperature. A higher phase treatment temperature and a longer phase treatment time can obtain a higher Nb3Sn ratio, but too high a phase treatment temperature and a phase treatment time will cause abnormal growth of Nb3Sn grains, resulting in a reduction in the number of grain boundaries in the Nb3Sn layer, which weakens the pinning effect of the grain boundaries on the magnetic flux. Therefore, by screening the phase treatment process, obtaining the optimal coupling relationship between the Nb3Sn ratio and the grain size is the key to improving the critical current density of superconducting wires. However, the existing Nb3Sn superconducting wire phase treatment process is extremely time-consuming. It takes a lot of time and cost to formulate different phase treatment processes using the "trial and error method" and analyze the organization and performance of the superconducting wire after phase treatment. In summary, there is an urgent need for a prediction method for the effect of the phase treatment process on the microstructure of Nb3Sn, which is helpful to quickly screen the phase treatment process of superconducting wires, avoid microstructure abnormalities caused by process instability, and reduce trial and error costs. Summary of the invention
[0004] The purpose of the present invention is to provide a Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening, which can effectively predict the influence of different phase formation temperatures and times on the Nb3Sn proportion and grain size, and reduce the time cost caused by batch testing.
[0005] The technical solution adopted by the present invention is a method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening, which is specifically implemented in the following steps:
[0006] Step 1, using a direct current hot pressing assisted sintering device to prepare a Cu-15Sn / Nb composite material using a Cu-15Sn alloy plate and a Nb plate, and generating a Nb3Sn superconducting layer at the Cu-15Sn / Nb interface to obtain a Cu-15Sn / Nb3Sn / Nb composite material;
[0007] Step 2, placing the Cu-15Sn / Nb3Sn / Nb composite material into a pressure device, and then performing phase treatment in a vacuum heat treatment furnace;
[0008] Step 3, statistically analyze the thickness and grain size of the Nb3Sn layer in the Cu-15Sn / Nb3Sn / Nb composite material after different phase forming process treatments, and then use the maximum inheritance algorithm to fit the Nb3Sn layer thickness and grain size according to the kinetic formula to obtain the changing trend of the Nb3Sn layer thickness and grain size with the phase forming time at different phase forming temperatures.
[0009] The present invention is also characterized in that:
[0010] Step 1 is as follows:
[0011] Step 1.1, rolling the Cu-15Sn alloy plate and the Nb plate, cutting them after rolling, grinding the cut Cu-15Sn alloy plate and the Nb plate with sandpaper, then pickling the Cu-15Sn alloy plate and the Nb plate with 10% HNO3, and finally ultrasonically cleaning them with anhydrous ethanol;
[0012] Step 1.2, stacking the ultrasonically cleaned Cu-15Sn alloy sheet and Nb sheet into a graphite mold equipped with upper and lower pressure rods, placing the graphite mold into a DC hot pressing assisted sintering device and adjusting the positions of the upper and lower pressure rods and the pressure head of the DC hot pressing assisted sintering device;
[0013] Step 1.3, setting a gradient temperature rise curve for the DC hot pressing assisted sintering equipment, and performing sintering treatment according to the set gradient temperature rise curve to obtain a Cu-15Sn / Nb3Sn / Nb composite material.
[0014] In step 1.1, the original thickness of the Cu-15Sn alloy plate and the Nb plate is 7 mm, the rolling deformation is 28-32%, and the single rolling deformation is 0.5-0.7 mm.
[0015] The size of the Cu-15Sn alloy plate and the Nb plate cut in step 1.1 is φ20 mm, and the ultrasonic cleaning time is 10 min.
[0016] The gradient heating curve of the DC hot pressing assisted sintering equipment in step 1.3 is set as follows:
[0017] Microstructure control stage: the temperature is raised from room temperature to 450°C, the heating current is 600A, and the temperature is kept at 450°C for 15 minutes;
[0018] After the microstructure regulation stage is completed, the diffusion stage of the sample is carried out. In this stage, the heating current is increased to 875A, and the temperature of the stacked Cu-15Sn alloy plate and Nb plate reaches 750-770°C. Then, a pressure of 30MPa is applied thereto. After the temperature reaches 750-770°C and the pressure reaches 30MPa, they are maintained for 110-120min to obtain a Cu-15Sn / Nb3Sn / Nb composite material.
[0019] When the sintering process is performed in the DC hot pressing assisted sintering equipment in step 1.3, the vacuum degree in the furnace of the DC hot pressing assisted sintering equipment is maintained at 2.0×10 -2 ~2.5×10 -2 Pa.
[0020] Step 2 is as follows:
[0021] The sintered Cu-15Sn / Nb3Sn / Nb composite material sample was taken out from the DC hot pressing assisted sintering device and cooled. Then, the Cu-15Sn / Nb3Sn / Nb composite material was placed in a pressure device, and then the pressure device was placed in a vacuum of 3.0×10 -1 Pa vacuum heat treatment furnace, phase treatment is carried out at a temperature of 750 to 810°C and a treatment time of 25 to 100 hours.
[0022] In step 2, the pressure device maintains a pressure of 1 MPa for the Cu-15Sn / Nb3Sn / Nb composite material sample during the phase forming process.
[0023] The kinetic formula in step 3 is:
[0024] y=kt n ;
[0025] R n -R0 n = rt;
[0026] Wherein, y and R are the thickness (μm) and grain size (μm) of the Nb3Sn layer after phase formation treatment, k and r are the growth constants of the Nb3Sn layer and grains, respectively, n is the growth coefficient, R0 is the grain size of the Nb3Sn layer after treatment by the DC hot pressing assisted sintering equipment in step 1.3, and t is the phase formation time, unit: h.
[0027] The variation trend of Nb3Sn layer thickness and grain size with phase formation time at different phase formation temperatures obtained in step 3 is as follows:
[0028] The thickness variation curve of the Nb3Sn layer at different phase forming temperatures and the phase forming time are obtained, and the grain size variation curve of the Nb3Sn layer at different phase forming temperatures and the phase forming time are obtained.
[0029] The intersection of the curves of the thickness of the Nb3Sn layer changing with the phase forming time at different phase forming temperatures and the curves of the grain size of the Nb3Sn layer changing with the phase forming time at different phase forming temperatures are obtained. The area between the two curves before the intersection time is the process selection area. The values of the left and right y-axes corresponding to any point in the process selection area are the predicted values of the thickness and grain size of the Nb3Sn layer at the temperature and time, respectively. The area between the two curves after the intersection time is the instability zone. The process corresponding to the instability zone cannot find the optimal coupling relationship between the thickness and grain size of the Nb3Sn layer.
[0030] The beneficial effects of the present invention are:
[0031] The present invention constructs a Nb3Sn superconducting layer at the Cu-15Sn / Nb interface under the synergistic effect of heat, force and electricity through DCHP. In the process, the introduction of the electric effect improves the migration speed of Cu, Sn and Nb atoms, and the introduction of mechanical pressure forms dislocation crystallographic defects in the sample, which changes the diffusion mode of Sn in the Nb3Sn layer from bulk diffusion to faster grain boundary diffusion, which is helpful to generate a high-proportion Nb3Sn phase in the subsequent phase forming process; by statistically analyzing the thickness of the Nb3Sn layer and the grain size in the sample under different phase forming processes, combining two kinetic formulas to describe the trend of the change of the Nb3Sn layer thickness and the grain size, it is possible to predict the microstructure of Nb3Sn and draw the instability range of the phase forming process to avoid abnormal growth of grains. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a trend diagram of the thickness change of Nb3Sn layer under different phase treatment processes in Examples 4-6 of the Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening of the present invention;
[0033] Figure 2 It is a trend diagram of the change of Nb3Sn grain size under different phase treatment processes in Examples 4-6 of the Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening of the present invention;
[0034] Figure 3 It is a Nb3Sn superconducting phase microstructure prediction diagram established by the present invention through Example 4 based on kinetic data screening;
[0035] Figure 4 It is a Nb3Sn superconducting phase microstructure prediction diagram established by the present invention through Examples 4-6 based on kinetic data screening;
[0036] Figure 5 is a microstructure diagram of the Nb3Sn layer after phase forming treatment at 782°C for 52h in Example 7 of the present invention;
[0037] Figure 6 This is a distribution diagram of the grain size in the Nb3Sn layer after phase forming treatment at 782°C for 52h in Example 7 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] Example 1
[0040] The Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening is implemented in the following steps:
[0041] Step 1, using a direct current hot pressing assisted sintering device (DCHP) to prepare a Cu-15Sn alloy plate and a Nb plate, and generating a Nb3Sn superconducting layer at the Cu-15Sn / Nb interface to obtain a Cu-15Sn / Nb3Sn / Nb composite material, specifically:
[0042] Step 1.1, rolling the Cu-15Sn alloy plate and the Nb plate, cutting them after rolling, grinding the cut Cu-15Sn alloy plate and the Nb plate with sandpaper, then pickling the Cu-15Sn alloy plate and the Nb plate with 10% HNO3, and finally ultrasonically cleaning them with anhydrous ethanol;
[0043] Step 1.2, stacking the ultrasonically cleaned Cu-15Sn alloy sheet and Nb sheet into a graphite mold equipped with upper and lower pressure rods, placing the graphite mold into a DC hot pressing assisted sintering device and adjusting the positions of the upper and lower pressure rods and the pressure head of the DC hot pressing assisted sintering device;
[0044] Step 1.3, setting a gradient temperature rise curve of a direct current hot pressing assisted sintering device, and performing a sintering process according to the set gradient temperature rise curve to obtain a Cu-15Sn / Nb3Sn / Nb composite material;
[0045] Step 2: Place the Cu-15Sn / Nb3Sn / Nb composite material into a pressure device, and then perform phase treatment in a vacuum heat treatment furnace, specifically: take out the sintered Cu-15Sn / Nb3Sn / Nb composite material sample from the DC hot pressing assisted sintering device and cool it, then place the Cu-15Sn / Nb3Sn / Nb composite material into a pressure device, and then place the pressure device into a vacuum furnace with a degree of vacuum of 3.0×10 -1Pa vacuum heat treatment furnace, phase treatment, treatment temperature is 750 ~ 810 ℃, treatment time is 25 ~ 100h;
[0046] Step 3, after different phase forming processes, the thickness and grain size of the Nb3Sn layer in the Cu-15Sn / Nb3Sn / Nb composite material are statistically analyzed, and then the maximum inheritance algorithm is used to fit the Nb3Sn layer thickness and grain size according to the kinetic formula to obtain the variation trend of the Nb3Sn layer thickness and grain size with the phase forming time at different phase forming temperatures;
[0047] The kinetic formula is:
[0048] y=kt n ;
[0049]
[0050] Wherein, y and R are the thickness (μm) and grain size (μm) of the Nb3Sn layer after phase formation, k and r are the growth constants of the Nb3Sn layer and grain, n is the growth coefficient, R0 is the grain size of the Nb3Sn layer after the DC hot pressing assisted sintering equipment in step 1.3, and t is the phase formation time, in h;
[0051] The variation trends of the thickness and grain size of the Nb3Sn layer with the phase forming time at different phase forming temperatures are obtained as follows: the variation curves of the thickness of the Nb3Sn layer with the phase forming time at different phase forming temperatures are obtained, and the variation curves of the grain size of the Nb3Sn layer with the phase forming time at different phase forming temperatures are obtained; with time as the horizontal coordinate, the layer thickness and grain size of the Nb3Sn layer as the left and right vertical coordinates, a prediction graph is drawn. In the prediction graph, there is an intersection between the variation curves of the thickness of the Nb3Sn layer with the phase forming time at different phase forming temperatures and the variation curves of the grain size of the Nb3Sn layer with the phase forming time at different phase forming temperatures. The area between the two curves before the intersection time is the process selection area. The values of the left and right y-axes corresponding to any point in the process selection area are the predicted values of the thickness of the Nb3Sn layer and the grain size at the temperature and time, respectively. The area between the two curves after the intersection time is the instability zone. The process corresponding to the instability zone cannot find the optimal coupling relationship between the thickness and grain size of the Nb3Sn layer.
[0052] Example 2
[0053] Based on Example 1, the original thickness of the Cu-15Sn alloy plate and the Nb plate in step 1.1 is 7 mm, the rolling deformation is 28-32%, and the single rolling deformation is 0.5-0.7 mm. The size of the Cu-15Sn alloy plate and the Nb plate after cutting in step 1.1 is φ20 mm, and the ultrasonic cleaning time is 10 min.
[0054] Example 3
[0055] Based on Example 2, the gradient heating curve of the DCHP assisted sintering equipment in step 1.3 is set as follows:
[0056] Microstructure control stage: the temperature is raised from room temperature to 450°C, the heating current is 600A, and the temperature is kept at 450°C for 15 minutes;
[0057] After the microstructure regulation stage is completed, the diffusion stage of the sample is carried out. In this stage, the heating current is increased to 875A, and the temperature of the stacked Cu-15Sn alloy plate and Nb plate reaches 750-770°C. Then, a pressure of 30MPa is applied thereto. After the temperature reaches 750-770°C and the pressure reaches 30MPa, they are maintained for 110-120min to obtain a Cu-15Sn / Nb3Sn / Nb composite material.
[0058] When the sintering process is carried out in the DC hot pressing assisted sintering equipment, the vacuum degree in the furnace of the DC hot pressing assisted sintering equipment is maintained at 2.0×10 -2 ~2.5×10 -2 Pa.
[0059] The present invention adopts DCHP to generate a Nb3Sn layer at the interface of Cu-15Sn alloy / Nb. In the process, a heating current of 600A is selected to heat the sample temperature to 450°C and keep the temperature for 15 minutes, so as to adjust the tin-rich phase type in the microstructure of the rolled Cu-15Sn alloy to the Cu3Sn phase. The gradient of the microscopic Sn atoms provided by the Cu3Sn phase is convenient for the subsequent generation of the Nb3Sn phase. A pressure of 30MPa is added in the diffusion stage carried out at 750-770°C. On the one hand, the introduction of stress can accelerate the mutual diffusion efficiency of Cu, Sn and Ti atoms, and on the other hand, provide crystallographic defects such as dislocations for the sample, so as to change the diffusion mode of Sn in the Nb3Sn layer from bulk diffusion to faster grain boundary diffusion. Under the synergistic effect of the two, it is helpful to quickly generate the Nb3Sn layer.
[0060] Under the synergistic effect of heat and electricity, the present invention makes the type of tin-rich phase in the Cu-15Sn alloy Cu3Sn before generating the Nb3Sn phase, constructs a microscopic concentration gradient that is conducive to the diffusion of the Sn element, and facilitates the subsequent generation of Nb3Sn. After the organizational regulation stage is over, the heating current is increased to 875A, and after the sample temperature reaches 750-770°C, a pressure of 30MPa is applied to it, and the above temperature and pressure are maintained for 110-120min to complete the diffusion stage of the sample, and a Nb3Sn layer is generated at the Cu-15Sn / Nb interface. The introduction of the electrical effect increases the migration speed of Cu, Sn, and Nb atoms, and constructs a Nb3Sn layer with a straight boundary in a relatively short time. The introduction of mechanical pressure during the diffusion process provides a diffusion driving force for the sample, which plays a positive role in the formation of the Nb3Sn layer. In addition, under the action of stress, the introduction of crystallographic defects such as dislocations in the sample changes the diffusion mode of Sn in the Nb3Sn layer from bulk diffusion to faster grain boundary diffusion, which helps to generate a high proportion of Nb3Sn phase in the subsequent phase formation process.
[0061] Example 4
[0062] On the basis of Example 3, the pressure device in step 2 maintains a pressure of 1 MPa for the Cu-15Sn / Nb3Sn / Nb composite material sample during the phase forming process.
[0063] Example 4
[0064] On the basis of Example 3, the method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening of the present invention is specifically as follows:
[0065] (1) Preparation of Nb3Sn superconducting phase: The Cu-15Sn alloy and Nb with a thickness of 7 mm were rolled, and the rolling deformation was 28%, and the single rolling deformation was 0.5 mm. After cutting into plates with a size of φ20, the surfaces of the Cu-15Sn alloy and Nb plates were polished using sandpapers of #600, #800, #1200, #1500, and #2000 in sequence. The Cu-15Sn alloy and Nb plates were pickled with 10% HNO3 and stacked in the graphite mold of the DCHP equipment;
[0066] (2) Turn on the three-stage vacuum pump system to maintain the vacuum degree in the DCHP equipment furnace at 2.0×10 -2Pa. Set up a gradient heating curve and heat the sample to 450°C with a heating current of 600A. After reaching the temperature, keep it warm for 15 minutes, then raise the sample temperature from 450°C to 750°C with a heating current of 875A and keep it warm for 110 minutes. While keeping warm, apply a pressure of 30MPa to the sample until the sample cools to room temperature. Load the DCHP sample into the pressure device so that the sample maintains a pressure of 1MPa during the phase formation process. Place the pressure device in a vacuum of 3.0×10 -1 Pa vacuum heat treatment furnace, the samples were subjected to phase treatment at a temperature of 750 ° C and a treatment time of 25h, 50h, 75h, and 100h.
[0067] (3) The statistical results show that Figure 1-2 As shown in the figure, when the processing temperature is 750℃, the corresponding Nb3Sn layer thickness is 5.9μm (25h), 11.8μm (50h), 15.3μm (75h), and 17.5μm (100h); the grain size is 0.17μm (25h), 0.17μm (50h), 0.19μm (75h), and 0.21μm (100h). The maximum inheritance algorithm is used to fit the above parameters. The equation for the change of Nb3Sn layer thickness with time is y=0.52x^0.77, and the equation for the change of Nb3Sn grain size with time is y=3.7×10^-5×exp(x / 17)+3.7×10^-5×exp(x / 17)+0.17. According to the intersection position, the instability interval and process selection area of abnormal growth of Nb3Sn grains at 750℃ are drawn.
[0068] Example 5
[0069] On the basis of Example 3, the method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening of the present invention is specifically as follows:
[0070] (1) Preparation of Nb3Sn superconducting phase: rolling treatment of Cu-15Sn alloy and Nb with a thickness of 7 mm, with a rolling deformation of 30% and a single rolling deformation of 0.5 mm. After cutting into plates with a size of φ20, the surfaces of the Cu-15Sn alloy and Nb plates were polished using sandpapers of #600, #800, #1200, #1500, and #2000 in sequence. After pickling the Cu-15Sn alloy and Nb plates with 10% HNO3, they were stacked in the graphite mold of the DCHP equipment.
[0071] (2) Turn on the three-stage vacuum pump system to maintain the vacuum degree in the DCHP equipment furnace at 2.2×10 -2Pa. Set up a gradient heating curve and heat the sample to 450°C with a heating current of 600A. After reaching the temperature, keep it warm for 15 minutes, then raise the sample temperature from 450°C to 760°C with a heating current of 875A and keep it warm for 110 minutes. While keeping warm, apply a pressure of 30MPa to the sample until the sample cools to room temperature. Load the DCHP sample into a pressure device to maintain a pressure of 1MPa during the phase formation process. Place the pressure device in a vacuum of 3.0×10 -1 Pa vacuum heat treatment furnace, the samples were subjected to phase treatment at a temperature of 770 ° C and a treatment time of 25h, 50h, 75h, and 100h.
[0072] (3) The statistical results show that Figure 1-2 As shown in the figure, when the processing temperature is 770℃, the thickness of the Nb3Sn layer is 11.8μm (25h), 15.2μm (50h), 19.5μm (75h), 21.5μm (100h), and the grain size is 0.21μm (25h), 0.23μm (50h), 0.24μm (75h), 0.42μm (100h). The maximum inheritance algorithm is used to fit the above parameters. The equation of the change of the Nb3Sn layer thickness with time is y=1.1x^0.68, and the equation of the change of the Nb3Sn grain size with time is y=1.3×10^-4×exp(x / 15.5)+2×10^-4×exp(x / 15.5)+0.21. According to the intersection position, the instability interval and process selection area of abnormal growth of Nb3Sn grains at 770℃ are drawn.
[0073] Example 6
[0074] On the basis of Example 3, the method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening of the present invention is specifically as follows:
[0075] (1) Preparation of Nb3Sn superconducting phase: rolling treatment of Cu-15Sn alloy and Nb with a thickness of 7 mm, with a rolling deformation of 32% and a single rolling deformation of 0.5 mm. After cutting into plates with a size of φ20, the surfaces of the Cu-15Sn alloy and Nb plates were polished using sandpapers of #600, #800, #1200, #1500, and #2000 in sequence. After pickling the Cu-15Sn alloy and Nb plates with 10% HNO3, they were stacked in the graphite mold of the DCHP equipment.
[0076] (2) Turn on the three-stage vacuum pump system to maintain the vacuum degree in the DCHP equipment furnace at 2.5×10 -2Pa. Set up a gradient heating curve and heat the sample to 450°C with a heating current of 600A. After reaching the temperature, keep it warm for 15 minutes, then raise the sample temperature from 450°C to 770°C with a heating current of 875A and keep it warm for 120 minutes. While keeping warm, apply a pressure of 30MPa to the sample until the sample cools to room temperature. Load the DCHP sample into the pressure device so that the sample maintains a pressure of 1MPa during the phase formation process. Place the pressure device in a vacuum of 3.0×10 -1 Pa vacuum heat treatment furnace, the samples were subjected to phase treatment at a temperature of 810 ° C and a treatment time of 25h, 50h, 75h, and 100h.
[0077] (3) The statistical results show that Figure 1-2 As shown in the figure, when the processing temperature is 810℃, the thickness of the Nb3Sn layer is 16.9μm (25h), 31.1μm (50h), 31.9μm (75h), 41.6μm (100h), and the grain size is 0.27μm (25h), 0.31μm (50h), 0.49 (75h), 1.28μm (100h). The maximum inheritance algorithm is used to fit the above parameters. The equation of the change of Nb3Sn layer thickness with time is y=2.9x^0.57, and the equation of the change of Nb3Sn grain size with time is y=2.4×10^-3×exp(x / 18.9)+2.8×10^-3×exp(x / 18.9)+0.26. According to the intersection position, the instability interval and process selection area of abnormal growth of Nb3Sn grains at 770℃ are drawn.
[0078] Example 7
[0079] On the basis of Examples 4-6, a prediction graph is drawn according to the equation of the change of Nb3Sn layer thickness over time and the equation of the change of Nb3Sn grain size over time. If it is a prediction of a single temperature, the two curves of the corresponding temperature are drawn on a curve graph to obtain the intersection point and the corresponding instability interval and process selection area, such as Figure 3 As shown in the figure, it is a prediction diagram at 750°C; if the prediction within the temperature range is obtained, the curves within the temperature range are superimposed to obtain, such as Figure 4 As shown, it is the prediction diagram for the range of 750-810°C.
[0080] In order to verify the reliability of the invention, the phase treatment temperature was set to 782°C and the phase treatment time was set to 52h. The microstructure of the sample after phase treatment is as follows: Figure 5 As shown in Figure 2, the distribution of grain size in the Nb3Sn layer is as follows: Figure 6 As shown in Figure 2, the width of the Nb3Sn layer of the sample after phase treatment is 23 μm, and the average grain size is 0.3 μm, which is consistent with Figure 4The prediction results are consistent with those in , which proves the reliability of the prediction method.
[0081] The present invention solves the problem of high screening time cost of bronze method phase treatment process by fitting the Nb3Sn layer thickness and grain size at different treatment temperatures with the help of kinetic equations, and finally obtains a Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening, which can effectively guide the screening of Nb3Sn phase treatment process and reduce the trial and error cost.
Claims
1. A method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening, characterized in that: The specific steps are as follows: Step 1, using a direct current hot pressing assisted sintering device to prepare a Cu-15Sn / Nb composite material using a Cu-15Sn alloy plate and a Nb plate, and generating a Nb3Sn superconducting layer at the Cu-15Sn / Nb interface to obtain a Cu-15Sn / Nb3Sn / Nb composite material; Step 2, placing the Cu-15Sn / Nb3Sn / Nb composite material into a pressure device, and then performing phase treatment in a vacuum heat treatment furnace; Step 3, statistically analyze the thickness and grain size of the Nb3Sn layer in the Cu-15Sn / Nb3Sn / Nb composite material after different phase forming process treatments, and then use the maximum inheritance algorithm to fit the Nb3Sn layer thickness and grain size according to the kinetic formula to obtain the changing trend of the Nb3Sn layer thickness and grain size with the phase forming time at different phase forming temperatures.
2. The Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening according to claim 1 is characterized in that: The step 1 is specifically as follows: Step 1.1, rolling the Cu-15Sn alloy plate and the Nb plate, cutting them after rolling, grinding the cut Cu-15Sn alloy plate and the Nb plate with sandpaper, then pickling the Cu-15Sn alloy plate and the Nb plate with 10% HNO3, and finally ultrasonically cleaning them with anhydrous ethanol; Step 1.2, stacking the ultrasonically cleaned Cu-15Sn alloy sheet and Nb sheet into a graphite mold equipped with upper and lower pressure rods, placing the graphite mold into a DC hot pressing assisted sintering device and adjusting the positions of the upper and lower pressure rods and the pressure head of the DC hot pressing assisted sintering device; Step 1.3, setting a gradient temperature rise curve for the DC hot pressing assisted sintering equipment, and performing sintering treatment according to the set gradient temperature rise curve to obtain a Cu-15Sn / Nb3Sn / Nb composite material.
3. The Nb3Sn superconducting phase microstructure prediction method based on kinetic data screening according to claim 2 is characterized in that: In the step 1.1, the original thickness of the Cu-15Sn alloy plate and the Nb plate is 7 mm, the rolling deformation is 28-32%, and the single rolling deformation is 0.5-0.7 mm; The size of the Cu-15Sn alloy plate and the Nb plate cut in step 1.1 is φ20 mm, and the ultrasonic cleaning time is 10 min.
4. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 3, characterized in that: The gradient heating curve of the DC hot pressing assisted sintering equipment in step 1.3 is set as follows: Microstructure control stage: the temperature is raised from room temperature to 450°C, the heating current is 600A, and the temperature is kept at 450°C for 15 minutes; After the microstructure regulation stage is completed, the diffusion stage of the sample is carried out. In this stage, the heating current is increased to 875A, and the temperature of the stacked Cu-15Sn alloy plate and Nb plate reaches 750-770°C. Then, a pressure of 30MPa is applied thereto. After the temperature reaches 750-770°C and the pressure reaches 30MPa, they are maintained for 110-120min to obtain a Cu-15Sn / Nb3Sn / Nb composite material.
5. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 4, characterized in that: When the sintering process is performed in the DC hot pressing assisted sintering equipment in step 1.3, the vacuum degree in the furnace body of the DC hot pressing assisted sintering equipment is maintained at 2.0×10 -2 ~2.5×10 -2 Pa.
6. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 5, characterized in that: The step 2 is specifically as follows: The sintered Cu-15Sn / Nb3Sn / Nb composite material sample was taken out from the DC hot pressing assisted sintering device and cooled. Then, the Cu-15Sn / Nb3Sn / Nb composite material was placed in a pressure device, and then the pressure device was placed in a vacuum of 3.0×10 -1 Pa vacuum heat treatment furnace, phase treatment is carried out at a temperature of 750 to 810°C and a treatment time of 25 to 100 hours.
7. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 6, characterized in that: The pressure device in step 2 maintains a pressure of 1 MPa for the Cu-15Sn / Nb3Sn / Nb composite material sample during the phase forming process.
8. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 7, characterized in that: The kinetic formula in step 3 is: y=kt n ; R n -R0 n =rt; Among them, y and R are the thickness and grain size of the Nb3Sn layer after phase formation treatment, respectively, the units of thickness and grain size are um, k and r are the growth constants of the Nb3Sn layer and grains, respectively, n is the growth coefficient, R0 is the grain size of the Nb3Sn layer after treatment with DC hot pressing assisted sintering equipment in step 1.3, and t is the phase formation time, unit is h.
9. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 8, characterized in that: The variation trend of the Nb3Sn layer thickness and grain size at different phase formation temperatures obtained in step 3 with the phase formation time is specifically as follows: The thickness variation curve of the Nb3Sn layer at different phase forming temperatures and the phase forming time are obtained, and the grain size variation curve of the Nb3Sn layer at different phase forming temperatures and the phase forming time are obtained.
10. The method for predicting the microstructure of Nb3Sn superconducting phase based on kinetic data screening according to claim 9, characterized in that: The intersection of the curves of the thickness of the Nb3Sn layer changing with the phase forming time at different phase forming temperatures and the curves of the grain size of the Nb3Sn layer changing with the phase forming time at different phase forming temperatures are obtained. The area between the two curves before the intersection time is the process selection area. The values of the left and right y-axes corresponding to any point in the process selection area are the predicted values of the thickness and grain size of the Nb3Sn layer at the temperature and time, respectively. The area between the two curves after the intersection time is the instability zone. The process corresponding to the instability zone cannot find the optimal coupling relationship between the thickness and grain size of the Nb3Sn layer.